1, 3, 4-Thiadiazole Derivatives. Part 91. Synthesis and Biological Activity of Metal Complexes of 5-(2-Aminoethyl)-2-Amino-1, 3, 4-Thiadiazole. Issue 5 (1996) - Barboiu Barboiu, Mihai Mihai; Cimpoesu Cimpoesu, Marilena Marilena; Guran Guran, Cornelia Cornelia; Supuran Supuran, Claudiu T. Claudiu T.
Abstract : Metal complexes of the title ligand (L) containing Co(II), Ni(II) and Cu(II) were prepared and characterized by elemental analysis, IR, electronic spectroscopy and conductimetry. The new derivatives, possessing the following formulae, CuL 2 ( OH ) 2, NiL 2 Cl 2, and [ Co 2 LCl 4 ] n showed in vitro antifungal activity against Aspergillus and Candida spp.